Large urban freight traffic generators: Opportunities for city logistics initiatives - Jaller, Miguel; Wang, Xiaokun (Cara); Holguin-Veras, Jose (Journal of Transport and Land Use, 2015)
This paper develops procedures to identify and quantify the role played by large urban freight traffic generators as contributors of truck traffic in metropolitan areas. Although ports, container terminals, and other industrial sites are usually associated with large generations of truck trips, they only represent a small proportion of the total trips produced and attracted in large metropolitan areas. This paper analyzes the importance of other facilities such as ordinary businesses or buildings that individually or collectively (clusters) generate a large proportion of truck traffic. The paper discusses the opportunities of these large traffic generators for city logistics initiatives. In addition, the paper introduces two effective and complementary procedures to identify these generators using freight trip generation models estimated by the authors.